PENGKODEAN DALAM PEMBELAJARAN PENULISAN SASTRA - Tsalits Abdul Aziz Al farisi (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2020)
The purpose of this research is to describe it 1) how is the coding system for creating poetry. 2) how can student understand objects in the ward then applied to the text of diction. 3) how can students create certain diction in relation to what one imagines. The methods in this research are using quantitatif methods with model design patterns using media as a basis for finding a purpose the study of literature at SMA Kanjeng Sepuh school X class. The result of this study is the observation table of assessments stuents interest in literature especially the poem. On other side of the observation of teacher and student activities carrying out the study of poetry is also a focus quantitatif data results. The conclusion of this study is to find a point of literary learning accuracy through quantitatif measures in coding systems. It needs to be used to find the concrete steps the literary writing learning pattern that currently is of little interest to students.